ELECTRICAL INSTALLATION PLANNING IN THE HAJJ DORMITORY BUILDING OF PONTIANAK CITY - Julhafiz, Ridho Nur (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
The Hajj Dormitory Building in Pontianak City is a new four-story facility designed as a transit hub for Hajj pilgrims in West Kalimantan. This study aims to design a safe, reliable, and standard-compliant electrical installation to support the building's operations. The planning process is based on SNI 03-6197-2020 for lighting installations and PUIL 2020 for cable sizing, protective devices, and voltage drop requirements. The methods used include manual calculations for power requirements, voltage drop simulations using ETAP 21, and electrical installation design using AutoCAD software. The results indicate that the building requires a total power of 310,151 VA. The installation utilizes 2x(4x150 mm ²) cables and a Circuit Breaker (CB) with a 630A rating. A 400 kVA generator set is needed to provide backup power. Voltage drop simulations using ETAP 21 show a value of 0.163% from PLN to the Main Distribution Panel (MDP), which is within the maximum limit set by PUIL 2020 (â‰¤ 4%). This electrical installation plan ensures that the electrical system of the Hajj Dormitory Building operates efficiently and meets safety and reliability standards. The findings of this study can serve as a reference for implementing the building"™s electrical installation.